First Report of Bacillus Marisflavi as a Potential Pectinase Producing Bacteria From Samples of Savar, Dhaka - Afrin , Nazia; Shilpi , Rasheda Yasmin (Bangladesh Journal of Botany, 2023)
Pectin is a principal component of all plants' primary cell walls which can be hydrolyzed by pectinase enzymes. The present research was aimed at the isolation, screening and identification of pectinase producing bacteria from samples collected from jute degrading soil and water, rotten leaves, sawdust, and kitchen wastes. Out of 14 isolates, nine showed positive pectinolytic activity. Identification of Bacillus spp was done on the basis of morphological, cultural and biochemical characterization and Bacillus marisflavi(PSD2) by 16S rRNA sequencing. This is the first study to report Bacillus marisflavi as a significant pectinase producing bacteria from the world.Among the pectinase producing strains, Bacillus marisflavi(PSD2) showed the best pectinase activity (zone size 69 mm) and the pectinolytic activity observed was 0.61 IU/ml.The present study suggests Bacillus marisflavi as a potential source for pectinase enzyme and could be used in industrial production upon further investigation. Bangladesh J. Bot. 52(1): 159-163, 2023 (March)